EDUPRENEURSHIP SEBAGAI STRATEGI DAYA SAING USAHA MIKRO, KECIL, DAN MENENGAH DI JAWA TIMUR MENGHADAPI MEA - Wahyudi, Alexander (JURNAL AKUNTANSI DAN MANAJEMEN, 2017)
Education is the answer to disseminate entrepreneurial spirit and skills to the perpetrators of Micro, Small and Medium Enterprises (SME’s) in East Java. So education entrepreneurship education program that introduces the concepts of entrepreneurship which is equipped with a variety of sample application called edupreneurship will empower SMEs in East Java. At present, as many as 6.8 million SMEs spread across 38 districts/cities in East Java are still many obstacles. Among others, human resources (HR), business management, product quality, access capital, market access, business network, as well as in the field of competitiveness. For eliminating the constraints of the SMEs in East Java accompanied by the cooperative that currently as many as 30 754 units with a value-added contribution of 54.48 per cent in Gross Domestic Product per year in East Java. Through this background, the authors wanted to examine entrepreneurial leadership of the SMEs in East Java and then create strategies and programs that will be delivered edupreneurship. This study uses a qualitative method with secondary data as a research tool. This study shows that the entrepreneurship module to be delivered need to be tailored to the needs of SMEs and implemented in a sustainable manner.